Perception of Time in Music in Patients with Parkinson's Disease–The Processing of Musical Syntax Compensates for Rhythmic Deficits - Bellinger, Daniel; Altenmüller, Eckart; Volkmann, Jens (Frontiers in Neuroscience, 2017)
Objective: Perception of time as well as rhythm in musical structures rely on complex brain mechanisms and require an extended network of multiple neural sources. They are therefore sensitive to impairment. Several psychophysical studies have shown that patients with Parkinson´s disease (PD) have deficits in perceiving time and rhythms due to a malfunction of the basal ganglia (BG) network. Method: In this study we investigated the time perception of PD patients during music perception by assessing their just noticeable difference (JND) in the time perception of a complex musical Gestalt. We applied a temporal discrimination task using a short melody with a clear beat-based rhythm. Among the subjects, 26 patients under L-Dopa administration and 21 age-matched controls had to detect an artificially delayed time interval in the range between 80 and 300 milliseconds in the middle of the musical period. We analyzed the data by a) calculating the detection threshold directly, b) by extrapolating the JNDs, c.) relating it to musical expertise. Results: Patients differed from controls in the detection of time-intervals between 220-300ms (*p = 0.0200, n = 47). Furthermore, this deficit depended on the severity of the disease (*p = 0.0452; n = 47). Surprisingly, PD patients did not show any deficit of their JND compared to healthy controls, although the results showed a trend (*p = 0.0565, n = 40). Furthermore, no significant difference of the JND was found according to the severity of the disease. Additionally, musically trained persons seemed to have lower thresholds in detecting deviations in time and syntactic structures of music (*p = 0.0343, n = 39). Conclusion: As an explanation of these results, we would like to propose the hypothesis of a time-syntax-congruency in music perception suggesting that processing of time and rhythm is a Gestalt process and that cortical areas involved in processing of musical syntax may compensate for impaired BG circuits that are responsible for time processing and rhythm perception. This mechanism may emerge more strongly as the deficits in time processing and rhythm perception progress. Furthermore, we presume that top-down-bottom-up-processes interfere additionally and interact in this context of compensation.